(untitled) (Asian Journal of Medical and Biological Research, 2021)
COVID-19 is one of the most serious global public health threats creating an alarming situation. Therefore, there is an urgent need for investigating and predicting COVID-19 incidence to control its spread more effectively. This study aim to forecast the expected number of daily total confirmed cases, total confirmed new cases, total deaths and total new deaths of COVID-19 in Bangladesh for next 3 weeks. The number of daily total confirmed cases, total confirmed new cases, total deaths and total new deaths of COVID-19 from 8 March2020 to 4 February, 2021 was collected to fit an Autoregressive Integrated Moving Average (ARIMA) model to forecast the spread of COVID-19 in Bangladesh from 5th February 2021 to 25th February 2021. All statistical analyses were conducted using R-3.6.3 software with a significant level of p< 0.05. The ARIMA (1,2,1), ARIMA (1,1,1), ARIMA (1,2,2) and ARIMA (1,1,2) model was adopted for forecasting the number of daily total confirmed cases, total confirmed new cases, total deaths and new deaths of COVID-19, respectively. The results showed that an upward trend for the total confirmed cases and total deaths, while total confirmed new cases and total new death, will become stable in the next 3 weeks if prevention measures are strictly followed to limit the spread of COVID-19. The forecasting results of COVID-19 will not be dreadful for upcoming days in Bangladesh. However, the government and health authorities should take new approaches and keep strong monitoring of the existing strategies to control the further spread of this pandemic. Asian J. Med. Biol. Res. March 2021, 7(1): 21-32